HIV-1 Drug Resistance and Second-Line Treatment in Children Randomized to Switch at Low Versus Higher RNA Thresholds. (1st September 2015) - Harrison, Linda; Melvin, Ann; Fiscus, Susan; Saidi, Yacine; Nastouli, Eleni; Harper, Lynda; Compagnucci, Alexandra; Babiker, Abdel; McKinney, Ross; Gibb, Diana; Tudor-Williams, Gareth
Abstract : Background: The PENPACT-1 trial compared virologic thresholds to determine when to switch to second-line antiretroviral therapy (ART). Using PENPACT-1 data, we aimed to describe HIV-1 drug resistance accumulation on first-line ART by virologic threshold. Methods: PENPACT-1 had a 2 × 2 factorial design, randomizing HIV-infected children to start protease inhibitor (PI) versus nonnucleoside reverse transcriptase inhibitor (NNRTI)-based ART, and switch at a 1000 copies/mL versus 30, 000 copies/mL threshold. Switch criteria were not achieving the threshold by week 24, confirmed rebound above the threshold thereafter, or Center for Disease Control and Prevention stage C event. Resistance tests were performed on samples ≥1000 copies/mL before switch, resuppression, and at 4-years/trial end. Results: Sixty-seven children started PI-based ART and were randomized to switch at 1000 copies/mL (PI-1000), 64 PIs and 30, 000 copies/mL (PI-30, 000), 67 NNRTIs and 1000 copies/mL (NNRTI-1000), and 65 NNRTI and 30, 000 copies/mL (NNRTI-30, 000). Ninety-four (36%) children reached the 1000 copies/mL switch criteria during 5-year follow-up. In 30, 000 copies/mL threshold arms, median time from 1000 to 30, 000 copies/mL switch criteria was 58 (PI) versus 80 (NNRTI) weeks ( P = 0.81). In NNRTI-30, 000, more nucleoside reverse transcriptase inhibitor (NRTI) resistance mutations accumulated than other groups. NNRTI mutations were selected before switching at 1000 copies/mL (23% NNRTI-1000, 27% NNRTI-30, 000). Sixty-two children started abacavir + lamivudine, 166 lamivudine + zidovudine or stavudine, and 35 other NRTIs. The abacavir + lamivudine group acquired fewest NRTI mutations. Of 60 switched to second-line, 79% PI-1000, 63% PI-30, 000, 64% NNRTI-1000, and 100% NNRTI-30, 000 were <400 copies/mL 24 weeks later. Conclusions: Children on first-line NNRTI-based ART who were randomized to switch at a higher virologic threshold developed the most resistance, yet resuppressed on second-line. An abacavir + lamivudine NRTI combination seemed protective against development of NRTI resistance. Abstract : Supplemental Digital Content is Available in the Text.